Analysis of Lean Manufacturing Implementation With Value Stream Mapping and Failure Mode And Effect Analysis Method - D, Muhammad Yafi; Rusindiyanto, Rusindiyanto (Newinera Publisher, 2025)
PT. XYZ is a company that focuses on batik cloth production. This company produces batik cloth manually or what is commonly called mencanting. In its production process, PT. XYZ experiences obstacles in the form of waste problems. One effort to reduce or reduce this waste is by identifying the root of the waste that is occurring. Therefore, research was conducted using the lean manufacturing method and the help of value stream mapping to map the entire production process flow to make it easier to identify activities or processes that do not have a good impact. Then failure mode and effect analysis were also used to determine what priorities needed to be handled first so that this waste did not worsen production activities. From the results of the study, waste of the types of Defect, waiting, excess processing, excess inventory, and overproduction were obtained. The proposed improvements that can be given are eliminating unnecessary activities, conducting routine inspections of tools and machines, and creating a routine schedule for maintenance of tools and machines. In addition, it is also necessary to take firm action on the condition of employees, tools, and machines so that they are always maintained and always optimal.